Comparison between the measured and extracted values according to the equations in the NOVO SPT program - abood, maria; Aljanabi, Khalid; Sayl, Khamis (Iraqi Journal of Civil Engineering, 2024)
The evaluation of undrained shear strength (Su) in fine-grained soils is crucial for geotechnical engineering applications. This study aims to assess Su in fine-grained soils through laboratory testing and data analysis by different equations Su Undrained shear strength from field and Based on SPT-N Values. The introduction provides an overview of the importance of Su in geotechnical engineering and highlights the complexity of estimating Su in fine-grained soils. The material and methods section describes the collection of soil samples from Fallujah, which predominantly consist of silty clay and clayey silt. Field investigations were conducted to obtain Su measurements using field vane shear tests. The section also provides details on the field-testing data, including borehole depth, SPT results, consistency, Su, Su from SPT NOVO, and soil description. The laboratory testing and data analysis section presents the results of laboratory shear testing conducted on the collected soil samples. The testing involved determining the undrained shear strength of the soils using appropriate testing apparatus and procedures. The data obtained from the laboratory testing are analyzed to identify trends in Su and soil consistency. Based on the analysis of the data and the results obtained from the laboratory testing, it can be concluded that there is a relatively weak correlation between the undrained shear strength (Su) and the Standard Penetration Test (SPT) N-value. The correlations proposed by Sowers (1979), Kulhawy and Mayne (1990), Reese, Touma, and O'Neill (1976), and Terzaghi and Peck (1967) all show modest R2 values, indicating limited correlation between Su and N-value